FORMATION OF SCHOOLCHILDREN'S COGNITIVE INTEREST IN LEARNING IN THE LESSONS FROM ART CULTURE - O.V. Chebotarenko (Academy of Cognitive and Natural Sciences, 2022)
In the article the concept "cognitive concern" is esteemed and its levels are investigated. The conditions of increase of a level of cognitive concern learning on lessons of the world art culture with usage of synthesis o f arts are designed.